2015
DOI: 10.1016/j.jcjd.2014.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Performance-Based Financial Incentives for Diabetes Care: An Effective Strategy?

Abstract: The use of financial incentives provided to primary care physicians who achieve target management or clinical outcomes has been advocated to support the fulfillment of care recommendations for patients with diabetes. This article explores the characteristics of incentive models implemented in the context of universal healthcare systems in the United Kingdom, Australia, Taiwan and Canada; the extent to which these interventions have been successful in improving diabetes outcomes; and the key challenges and conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 32 publications
1
21
0
Order By: Relevance
“…Apart from this, there are researches directly revealed that P4P actually had a very limited function, and process indicators had higher rates of improvement than that of endpoint indicators. As Coleman et al presented, the rate of HbA1c screening (a process outcome) increased while the blood glucose level (an endpoint outcome) remained unchanged, which was also confirmed by Latham and Marshall . Considering all above, other factors, besides P4P, need to be considered so that the clinical performance can objectively be evaluated and truly improved on the basis of diverse baselines, which was similar to the previous studies .…”
Section: Discussionsupporting
confidence: 64%
“…Apart from this, there are researches directly revealed that P4P actually had a very limited function, and process indicators had higher rates of improvement than that of endpoint indicators. As Coleman et al presented, the rate of HbA1c screening (a process outcome) increased while the blood glucose level (an endpoint outcome) remained unchanged, which was also confirmed by Latham and Marshall . Considering all above, other factors, besides P4P, need to be considered so that the clinical performance can objectively be evaluated and truly improved on the basis of diverse baselines, which was similar to the previous studies .…”
Section: Discussionsupporting
confidence: 64%
“…Perhaps engagement with diabetes health care services could be promoted if equipment subsidies were conditional on this. Financial incentives for health care professionals could also be considered, although their influence on outcomes have not been demonstrated …”
Section: Discussionmentioning
confidence: 99%
“…This might be related to the use of quality‐of‐care measures such as comparing provider performance or the use of performance incentives . In other areas in the world founded on the presumption that guideline‐based care will generate savings by reducing demands on costly hospital‐based services over the long‐term incentive programmes aimed at improving diabetes outcomes are increasing in popularity . The concept of measuring the effectiveness among diabetes care providers is not new.…”
Section: Discussionmentioning
confidence: 99%